Analisis Potensi dan Strategi Pemanfaatan Limbah Kelapa Sawit di Kabupaten Labuhanbatu - Harahap, Sutan; Lubis, Zulkifli; Rahman, Abdul (Universitas Medan Area, 2019)
This study is to find out how much the potential for solid and liquid waste produced by oil palm plantations in the study area, methods of utilizing palm oil waste in the study area, and to determine the priority strategies for the utilization of palm oil waste in Labuhanbatu Regency. Based on the IFAS matrix, the x-axis is obtained = 1.02 and from the EFAS matrix, the y-axis is obtained = 0.45 so that (x, y) = (1.02,0.45) is in quadrant I (positive, positive). PT Pangkat Indonesia's SWOT quadrant matrix where the position shows PT Pangkat Indonesia as a strong and potential company, the strategy recommendations provided are potential, meaning that the company is in prime and stable condition so that it is possible to continue to carry out large potentials, increase growth and make progress in a progressive manner in the treatment of solid and liquid waste. Furthermore, the SWOT matrix is used based on the results of the classification of various possibilities of internal and external factors to facilitate decision making. Based on the IFAS matrix, the x-axis is obtained = 1.02 and the EFAS matrix is obtained by the y-axis = 0.45 so that (x, y) = (1.41.0.64) is in quadrant I (positive, positive). PT Sinar Pendawa's SWOT quadrant matrix where the position shows PT Sinar Pendawa as a strong and potential company, the strategy recommendations given are potential.